THE MEANING OF THE FINGER-CUTTING TRADITION IN THE PAPUA DANI TRIBE (STUDY IN SANOBA VILLAGE, NABIRE DISTRICT) - Helena Wonawai; Herman Utang; Imanta Immanuel Perangin-Angin; Aelsthri Ndandara (Jurnal Pluralis, 2024)
Tradition is a habit that is passed down from generation to generation, including various cultural values which include customs, belief systems, and so on. In this case the tradition of cutting the finger in the Dani tribe is a tradition that is quite extreme, but it still survives to this day and makes me interested to find out what meaning is contained in this tradition. The problem in this research is how is the tradition of cutting fingers in the Dani tribe and what is the meaning of cutting fingers that makes this tradition still maintained? The purpose of this study is to find out how the tradition of cutting fingers in the Dani tribe and what is the meaning of cutting fingers in the Dani tribe that makes this tradition still being maintained. This study uses the theory of symbolic interactionism. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, documentation. The informants in this study totaled 11 people consisting of 1 tribal chief, 1 village head, 2 traditional elders and 7 community leaders, who had an important role or who carried out the Finger Cutting Tradition. The results of this study indicate that the finger-cutting tradition is a quite extreme tradition in which this tradition is carried out by cutting off parts of the human body (fingers to hands) to make a symbol. Cutting your own finger is done directly without a good medical examination to ensure the person's health before carrying out the finger cutting tradition. What they did after hearing the sad news was to immediately tie the finger or hand that was going to be cut off using a rope until the hand or finger was no longer felt, then they would immediately cut it off with a sharp tool such as a knife or machete which they thought was sharp and could be used for cut. Even after cutting their fingers or hands, they immediately cover the wound with soft soil and wrap it in leaves and then tie it using the used cloth they have. Even after cutting their finger they did not carry out treatment through a medical team or something like that, they only used soft soil, leaves and makeshift cloth until the wound healed. They also cut their fingers without using special tools and not in special places. The Dani people are quite fanatical in that they believe that by simply cutting their finger they can avoid the calamity and bad luck that befalls them in the form of family grief and successive illnesses in the family. It is proven that the finger-cutting tradition has several meanings in it, including social meaning or a symbol of affection for their loved ones such as from husband to wife, parents to children or vice versa, religious meaning or belief in something, cultural and moral meaning. or a custom that has been passed down from generation to generation to the present day. They think that if they don't do it, they will no longer be respected by family members who have carried out the tradition. However, this meaning is still not recognized and understood by the current generation, so the researchers suggest that the community, the government's traditional elders continue to preserve this finger-cutting tradition properly so that it can be passed on to future generations and all Dani people, especially in the village of Sanoba. in order to maintain and maintain this tradition.